Intrahepatic bile duct primary cilia in biliary atresia. Issue 8 (19th February 2018) - Frassetto, Roberta; Parolini, Filippo; Marceddu, Salvatore; Satta, Giulia; Papacciuoli, Valeria; Pinna, Maria Antonia; Mela, Alessandra; Secchi, Giannina; Galleri, Grazia; Manetti, Roberto; Bercich, Luisa; Villanacci, Vincenzo; et al.
Abstract : Aim: The etiopathogenesis of non‐syndromic biliary atresia (BA) is obscure. The primary aim was to investigate intrahepatic bile duct cilia (IHBC) in BA at diagnosis and its correlation with clinical outcome. The secondary aim was to analyze IHBC in routine paraffin‐embedded liver biopsies using conventional scanning electron microscopy (SEM). Methods: Surgical liver biopsies taken at diagnosis from 22 BA infants (age range, 39–116 days) and from eight children with non‐BA chronic cholestasis (age range, 162 days −16.8 years) were evaluated for IHBC by immunofluorescence (IF) and SEM. A minimum 18‐month follow‐up after surgery was available for all patients. Results: By IF, cilia were present in 6/8 (75%) non‐BA but only in 3/22 (14%) BA cases, and cilia were reduced or absent in 19/22 (86%) BA and 2/8 (25%) non‐BA livers ( P < 0.01). In BA, cilia presence was found to be associated with clearance of jaundice at 6‐month follow‐up ( P < 0.05). However, high overall survival rates with native liver, >90% at 12 months, and >70% at 24 months post‐surgery, were recorded regardless of cilia presence/absence at diagnosis. Electron microscopy was able to detect bile ducts and cilia in routine liver biopsies, revealing significant abnormalities in 100% BA livers. Conclusions: The presence of IHBC in BA livers at the diagnosis was associated with resolution of cholestasis, although was not predictive of short‐term survival with native liver. Scanning electron microscopy represents a powerful new tool to study routine liver biopsies in biliary disorders. Cilia dysfunction in BA pathogenesis and/or disease progression warrants further investigation.